Immersion: An introduction to blue humanities - Batalla, Oriol (2025)
This article provides an introductory exploration of the interdisciplinary field of Blue Humanities. It seeks to bridge historical materialism and new materialisms to address the ecological crisis through a conceptual framework grounded in aquatic mediums. The study further unpacks the notion of corrosive materialities as both metaphor and practice, aimed at dismantling anthropocentric thought and fostering situated knowledge rooted in specific material and ecological contexts. Rather than proposing a fixed theory, the article offers a flexible framework for situated theorizing, culminating in a reflection on hydro-realism as a lens to understand planetary transformations beyond the confines of the climate paradigm.